Do hazardous manual handling task risk assessment methods align with systems thinking?. (August 2021) - McCormack, Peter; Read, Gemma J.M.; Goode, Natassia; Salmon, Paul M.
Highlights: Systematic review of 218 publications on hazardous manual handling (HMH) methods. HMH methods primarily assess risk factors at the staff and work levels. Application of HMH methods by practitioners identified controls mainly at the staff and work levels. Risk controls implementation was usually at the management level. A systems thinking approach in the HMH domain is not prevalent in the development of risk controls. Abstract: Musculoskeletal disorders caused by hazardous manual handling (HMH) create a significant burden on society and detriment to the daily activities of the injured person. It is widely accepted in safety science that systems thinking is the most suitable approach to safety management, but its adoption in the HMH context remains unclear. The aim of this systematic review was to evaluate the extent to which existing observation-based HMH risk assessment methods align with systems thinking. The risks assessed by HMH methods and the risk controls identified based on the application of each method were assessed for alignment with a systems thinking framework. The results show that existing HMH risk assessment methods are not aligned with systems thinking and the risk controls identified from the application of HMH methods primarily reside with the task, worker and management. Areas were identified that would contribute to the application of systems thinking in HMH risk assessment; (1) developing safety practitioner knowledge of systems thinking; and (2) providing safety practitioners with new methods to support systems thinking in HMH risk assessment.